Analysis Of The Preparation Of Sak-Emkm Financial Statements At The Jaya Mart Small And Medium Enterprise In The Village Of Gading Jaya, Mukomuko Regency - Devaliya, Devaliya; Kresnawati , Kresnawati; Astuty , Kamelia (Universitas Dehasen Bengkulu, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an essential sector in Indonesia’s economy, playing a major role in economic growth and employment. However, most MSME owners still face challenges in preparing financial statements in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM). One such enterprise is Toko Jaya Mart, located in Gading Jaya Village, Mukomuko Regency, which still records transactions manually and in an unstructured manner. This study aims to analyze the process of preparing financial statements at Toko Jaya Mart and assess their compliance with SAK-EMKM. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The results show that before implementing SAK-EMKM, Toko Jaya Mart had not yet separated assets, liabilities, income, and operating expenses. After adjustments were made, the financial statements were prepared in accordance with SAK-EMKM, including the Statement of Financial Position, Income Statement, and Notes to the Financial Statements. Nevertheless, there are still shortcomings, particularly in preparing the notes to the financial statements and in the owner’s understanding of accounting. Overall, the implementation of SAK-EMKM has improved the regularity and transparency of the business’s financial reporting.